Difference in frequency and outcome of geriatric emergency department utilization between urban and rural areas. Issue 4 (April 2019) - Ko, Ming-Chung; Lien, Hsin-Yi; Woung, Lin-Chung; Chen, Chin-Yi; Chen, Yu-Ling; Chen, Chu-Chieh
Abstract : Background: Elderly people are susceptible to develop multiple chronic diseases and are thus likely to utilize the emergency department (ED). Access to health care and health outcomes may differ between rural and urban areas. This study aims to compare the frequency and outcome of geriatric ED utilization between urban and rural areas. Methods: This population-based study obtained information from the health insurance database. The frequency and outcome of ED utilization in 2013 were compared among people aged ≥65 years living in urban and rural areas. The independent effect of various characteristics on the frequency and outcome of ED utilization was evaluated using multivariate logistic regression analysis. Results: Of the 6695 people living in urban areas, 1879 (28.07%) utilized the ED and accounted for 3859 ED visits. Meanwhile, 908 (29.75%) of the 3052 people living in rural areas utilized the ED and accounted for 1820 ED visits. No difference in the prevalence of ED utilization was found between the urban and rural areas. Urbanization did not affect the risk of frequent ED utilization among ED users. People living in rural areas had an increased risk of ED visits with a high acuity (adjusted odds ratio: 1.40, 95% CI: 1.12-1.75). Urbanization did not affect the risk of hospitalization or immediate death after ED visits. Conclusion: The frequency of ED utilization showed no urban-rural difference. Elderly people living in rural areas had an increased risk of visiting the ED with a high acuity.